Thin film nanocomposite membranes incorporated zirconium based metal organic frameworks for removal of lead(II) - Abdullah, Norfadhilatuladha (2020)
Contamination of heavy metals has attracted great attention in scientific community in which membrane technology by using thin film composite (TFC) membrane has shown a great potential for treating contaminated water. The presence of dense polyamide (PA) layer in TFC membrane often cause water transport to be hindered, yielding low flux at high pressure in which modifying TFC membranes by incorporating nanomaterials within thin active/selective layer serves as an interesting approach. This study aimed to develop and compare thin film nanocomposite (TFN) incorporated water-stable zirconium-based metal organic frameworks (MOFs) on the PA layer for removing lead (Pb) from water by different membrane processes. To investigate the effects of amine-functional groups of UiO-66 on physicochemical properties of the PA layer, TFN membranes with PA layer containing different loadings of UiO-66 or UiO-66-NH2 were prepared and compared followed by their performance test for Pb(II) removal. The synthesized UiO-66 and UiO-66-NH2 showed highly crystalline and uniform rhombic structures with particle size of 113-130 nm and 130-150 nm, respectively. Under field emission scanning electron microscopy analysis, the TFN membranes displayed thicker PA layer as compared to control membrane. Fourier transform infrared analysis revealed the successful fabrication of PA layer indicated by the strong amide peak. Atomic force microscopy analysis was similar for both TFN/UiO-66 and TFN/UiO-66-NH2 which resulted in rougher membrane surface. Water contact angle analysis showed improved hydrophilicty of TFN membranes as compared to control membrane, in which the hydrophilicity of TFN/UiO-66-NH2 was higher than TFN/UiO-66 membranes. Under nanofiltration (NF) process, it was found that the optimum loading of UiO-66 or UiO-66-NH2 (0.01 wt%) has shown higher pure water flux than control membrane (4.45 L/m2.h.bar), which was 6.26 L/m2.h.bar and 8.63 L/m2.h.bar, respectively. Basic salts rejections of MgSO4, Na2SO4, MgCl2 and NaCl revealed rejection of TFN membranes were at par with control membrane but at higher solute permeability. In terms of membrane performance for Pb(II) removal by NF process, increasing Pb(II) initial concentration caused decreased Pb(II) rejection for TFN/UiO-66 and TFN/UiO-66-NH2. Presence of cadmium (Cd)/nickel (Ni) decreased the rejection of Pb(II) ascribed by the hydrated size and diffusion coefficients of metals. Interestingly, under forward osmosis (FO) process, Pb(II) initial concentration and presence of Cd/Ni did not influence the rejection of Pb(II) in which 99% rejection was achieved for all membranes. TFN membranes which were TFN/UiO-66 and TFN/UiO-66-NH2 offered higher FO water flux, which was 16.51 L/m2.h and 18.51 L/m2.h, respectively as compared to 9.45 L/m2.h for control membrane. In comparison to NF process using the same membrane, the rejection via FO process was 30% more efficient. Stability study demonstrated 10% reduction of permeability of TFN membranes as compared to 15% permeability drop for control membrane when subjected to MgSO4 solution. The permeation and Pb(II) rejection from this study has proven that the incorporation of Zr-based MOFs (UiO-66 or UiO-66-NH2) as additive has improved the properties of TFN membranes making it suitable to be used for water/wastewater treatment.